2018
DOI: 10.5650/jos.ess18051
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Nanodisc Formation using Pxt-5 Peptide Isolated from Amphibian (<i>Xenopus tropicalis</i>) Skin, and its Altered Form, Modify-Pxt-5

Abstract: Nanodiscs are self-assembled discoidal nanoparticles composed of amphiphilic α-helical scaffold proteins or peptides that accumulate around the circumference of a lipid bilayer. In this study, Pxt-5, which is an antimicrobial peptide isolated from the skin of Xenopus tropicalis, and its modified peptide (Modify-Pxt-5) were synthesized by solid-phase peptide synthesis (SPPS).Their surface properties, which are an important factor in inducing nanodisc formation, were investigated by circular dichroism (CD) spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 32 publications
3
4
0
Order By: Relevance
“…ND 2, which displayed Cys at the peptide C-terminus afforded 16 ± 1 DNA strands per ND. These values are consistent with our simple calculations , that estimate that there are 4-fold more thiol groups on peptides compared to that of the phospholipids. Unsurprisingly, ND 3 displayed 25 ± 7 DNA strands per ND which suggests that DNA coupling can efficiently proceed on both the phospholipid and peptide with minimal steric clash.…”
Section: Resultssupporting
confidence: 92%
“…ND 2, which displayed Cys at the peptide C-terminus afforded 16 ± 1 DNA strands per ND. These values are consistent with our simple calculations , that estimate that there are 4-fold more thiol groups on peptides compared to that of the phospholipids. Unsurprisingly, ND 3 displayed 25 ± 7 DNA strands per ND which suggests that DNA coupling can efficiently proceed on both the phospholipid and peptide with minimal steric clash.…”
Section: Resultssupporting
confidence: 92%
“…Through experiments, it was demonstrated that these antimicrobial peptides could be efficiently incorporated into NDs, highlighting the potential for their application in antimicrobial therapies. 76 In conclusion, NDs offer substantial potential as versatile platforms for antibacterial and antiviral therapies. Their capability to deliver antimicrobial agents, induce specific immune responses, and be modified with various components significantly enhances the immunogenicity, specificity, and effectiveness of these therapeutic approaches.…”
Section: Antibacterial and Antiviral Therapymentioning
confidence: 99%
“…Through experiments, it was demonstrated that these antimicrobial peptides could be efficiently incorporated into NDs, highlighting the potential for their application in antimicrobial therapies. 76…”
Section: Application Of Nds In Disease Therapymentioning
confidence: 99%
“…This technique involves the spontaneous structural conversion of phospholipid vesicles (liposomes) into nanodiscs through the straightforward addition of amphiphilic peptides. These amphiphilic helical peptides function as a surfactant, adeptly solubilizing the phospholipid bilayer while stabilizing the edge of the bilayer’s rim [ 16 , 17 , 18 ]. Owing to their amphiphilic nature, these self-assembled structures prevent the exposure of the hydrophobic lipid core to aqueous media, thus providing relative stability and monodispersity.…”
Section: Introductionmentioning
confidence: 99%